1973
DOI: 10.1177/028418517301400510
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Complications following Needle Puncture of the Liver

Abstract: Needle biopsy and transhepatic cannulation of blood vessels and bile ducts of the liver have been used for several years. Owing to the proximity of the systems, short circuits may sometimes occur after puncture. It was therefore thought worthwhile to investigate experimentally possible vascular complications following the procedure.Material and Methods. Twenty-eight Swedish land rabbits, weighing between 1.4 and 3.4 kg, were anaesthetized with pentobarbitone sodium intravenously. A catheter (OPP 60, OD/ID 1.15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

1977
1977
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 8 publications
0
32
0
Order By: Relevance
“…The frequency of the arterio-portal shunt after puncturing the liver with a needle depended on the interval between the needle puncture and the hepatic arteriography, as high as 50% within the first week and less than 10% after the first week (18). The arterio-portal shunt tended to close spontaneously in time.…”
Section: Resultsmentioning
confidence: 96%
“…The frequency of the arterio-portal shunt after puncturing the liver with a needle depended on the interval between the needle puncture and the hepatic arteriography, as high as 50% within the first week and less than 10% after the first week (18). The arterio-portal shunt tended to close spontaneously in time.…”
Section: Resultsmentioning
confidence: 96%
“…In a prospective study, Okuda et al showed that 5.4% of 93 patients had evidence of an arterio portal fistula on hepatic angiography 3 days to 4 weeks after a percutaneous liver biopsy [6]. Many of the fistulae that are acquired through trauma spontaneously close with time, especially if they are small [3,5,9]. In addition to trauma, arterio portal fistulae can also develop from the rupture of a hepatic artery aneurysm into a portal vein or from a focal liver lesion such as a tumor [10].…”
Section: Discussionmentioning
confidence: 99%
“…A relatively high frequency of arterioportal shunt as a sequela of percutaneous needle biopsy has been described. Hellekant [17] reported that frequency of arteriovenous shunt depended on the interval between biopsy and angiography; incidence was as high as 50% in less than 1 week, dropping to 10% after 1 week. This confirms the tendency for a shunt to close spontaneously in time.…”
Section: Discussionmentioning
confidence: 99%